Experimental Investigation on Limit Cycle Wing Rock Effect on Wing Body Configuration Induced by Forebody Vortices - Rong,Zhen (2016)
ABSTRACT The purpose of this paper is to present the aerodynamic and flow characteristics of a slender body with a 30° swept wing configuration undergoing a limit cycle oscillation using a synchronous measurement and control technique of wing rock/particle image velocimetry/dynamic pressure associated with the time history of the wing rock motion. The experimental investigation was concentrated on 3 main areas: motion characteristics, static and dynamic surface pressures and static and dynamic particle image velocimetry. The tests’ results revealed that the lag in asymmetric twin vortices over the forebody switching from the left vortice pattern to the right one exhibits a hysteresis evolvement during the wing rock motion; the asymmetric triple vortices over the forebody interacted with the flowfield over wings appeared to induce the instability and damping moments. The main flow phenomena responsible for wing rock of wing body configuration were completely determined by the forebody vortices. These exhibit apparent dynamic hysteresis in vertical position, which further influences the wing flows, and the dynamic hysteresis of flows yields the damping moments sustaining the oscillations.